Seizures and early onset dementia: D2HGA1 inborn error of metabolism in adults. Issue 10 (28th August 2020) - Tabarestani, Sepideh; Varriano, Brenda; Rawal, Sapna; France Morel, Chantal; Carmela Tartaglia, Maria; Andrade, Danielle M.
Abstract: D‐2‐hydroxyglutaric aciduria type 1 (D2HGA1) is a rare inherited metabolic disorder usually manifesting in infancy/early childhood with seizures and significant central nervous system involvement. We report two siblings with D2HGA1 presenting with mild intellectual disability, and the onset of seizures in adulthood. One of them was misdiagnosed as tuberous sclerosis due to her presentation and the presence of subependymal nodules on brain imaging. Both further developed early onset dementia. This report expands the phenotype of D2HGA1 to include late‐onset seizures and early onset dementia in adults.